Instruments of the Innovation Companies’ Financing – New Opportunities of the Stock Exchange - Иван Иванович Родионов; А. С. Меньшикова (Journal of Corporate Finance Research / Корпоративные Финансы | ISSN: 2073-0438, 2012)
Author: Ivan Ivanovich Rodionov - National Research Institute "Higher School of Economics" irodionov@hse.ruDevelopment of instruments of financing of the innovation companies is the most important direction of support of economy’s modernization. Today the high-grade system of the state institutions of the development is created and performing such support, however mechanisms of attraction of private investments into the innovation companies are developed insufficiently. One of such mechanisms is the Innovation and Investments Market - special sector of MICEX-RTS, created for listing of the shares of innovation companies.